A modified biochar composite membrane and its preparation method and application
Through the preparation method of modified biochar composite film, the existing adsorbent materials have poor adsorption selectivity, insufficient stability and high cost in water treatment, and efficient and stable phosphate adsorption and salt reduction are achieved. Effects of plant growth.
Patent Information
- Application Number
- CN202410537300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The existing adsorbent materials have problems such as poor adsorption selectivity, insufficient stability and high cost in water treatment. In addition, salt ions affect plant growth during recycling of biochar materials, and PVC or PVDF biochar films do not under complex hydrological conditions. Stablize.
The modified biochar composite film is adopted, and the preparation method includes pyrolyzing peanut shell powder, bentonite powder, and dolomite powder to obtain modified biochar, complexing and cross-linking of chitosan succinic acid complex with Fe3+ to prepare phosphate blot polymerization The modified biochar was then mixed with the phosphate blot polymer and activated in water vapor, and finally mixed with the PVDF cast film liquid to form a film.
It improves the hydrophilicity of adsorbents and pollutant removal efficiency, reduces the impact of salt in high-salt wastewater on plant growth, and improves the structural safety and adsorption performance stability of the material.
Smart Images

Figure CN118204069B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorbent materials, and specifically relates to a modified biochar composite membrane and a preparation method and application thereof. Background Art
[0002] Phosphorus is a mineral nutrient necessary for the growth of organisms. It is involved in gene composition, cell membranes and energy conversion. It is also used in the manufacture of fertilizers, food additives, detergents and other products. With the growth of the global population and social economy, people's demand for phosphorus is also increasing. Excessive phosphorus entering the aquatic ecosystem will lead to eutrophication of rivers, lakes and reservoirs. Eutrophication of water bodies refers to the increase in the content of nutrients such as nitrogen (N) and phosphorus (P) in the water environment under the influence of human activities and natural factors. When it exceeds the upper limit of the water body, algae will reproduce in large numbers, the dissolved oxygen content of the water body will decrease, and the water quality environment will deteriorate, which will eventually lead to an imbalance in the water ecology and threaten the sustainable development of human society. In addition, at the current mining rate, phosphate mines will be exhausted in the next 50-100 years. Therefore, the removal and recovery of phosphates in water bodies are of great significance to water environment protection and human sustainable development.
[0003] At present, the main adsorbent materials used in water treatment are activated carbon, diatomaceous earth, zeolite, resin and nanomaterials, but these materials often have the following problems when used: (1) Activated carbon adsorbents are the most widely used, usually using their large specific surface area to capture pollutants through physical adsorption, so powdered activated carbon has better performance than granular activated carbon, but the adsorption selectivity is poor, and the pollutants after adsorption are unstable and easy to desorb; (2) Clay adsorbent materials usually have a negative charge on the surface, so they can only adsorb cationic pollutants, and the adsorption capacity and stability are poor. After absorbing water, swelling can easily cause turbidity in the water; (3) Although nanomaterial adsorbents have excellent performance, they are expensive and easy to agglomerate in water. It is difficult to separate solids from liquids, resulting in secondary pollution of water bodies and threatening human health through the food chain. Therefore, it is necessary to optimize the modification and solidification methods of adsorbents, develop environmentally friendly adsorbent materials with selective adsorption performance for specific pollutants, and study their structural safety and adsorption performance stability in complex water environments.
[0004] After existing biochar materials complete the saturated adsorption of pollutants, strong alkali is usually required to desorb and reuse them. When the maximum number of cycles is approached, they cannot be recycled, resulting in waste and are not conducive to carbon fixation and emission reduction. Returning them to the fields as fertilizer is a possible resource utilization method, but it is necessary to explore whether it is beneficial to plant growth and nutrient increase. For biochar materials that treat pollutants in high-salt wastewater, the biochar materials also adsorb salt ions during the adsorption process, resulting in a higher concentration of salt ions when returned to the fields, affecting plant growth.
[0005] In addition, the construction of PVC or PVDF biochar membranes can solve the problem of material separation and recycling to a certain extent. However, the addition of biochar materials will reduce the hydrophilicity of PVC or PVDF, so that the biochar materials cannot quickly and fully contact with pollutants, thereby affecting the pollutant adsorption rate per unit time. In actual use, PVC or PVDF biochar membranes also face problems such as instability and rupture under complex hydrological conditions or mechanical forces, causing difficulties in separation and recycling and secondary pollution. Summary of the invention
[0006] The purpose of the present invention is to provide a modified biochar composite membrane and a preparation method and application thereof.
[0007] The present invention discloses a method for preparing a modified biochar composite membrane, comprising the following steps:
[0008] Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900° C. for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1:(0.3-0.4):(0.3-0.6);
[0009] Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexing and cross-linking through epichlorohydrin, wherein the phosphate imprinted polymer has free hydroxyl groups; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1:(0.8-0.9);
[0010] The modified biochar and the phosphate imprinted polymer are mixed in a mass ratio of 1:(0.15-0.25), and activated in water vapor at 195-215° C. for 15-35 min to obtain a modified biochar composite material;
[0011] The modified biochar composite material is mixed with polyvinylidene fluoride (PVDF) casting solution, and the film is scraped with an automatic film applicator and then quickly placed in an aqueous solution to form a film through a phase conversion method. The film is a modified biochar composite film.
[0012] In a preferred embodiment, the mass fraction of the modified biochar composite material in the casting solution is 8-12%, the mass fraction of polyvinylidene fluoride (PVDF) in the casting solution is 6-10%, and the casting solution further contains a pore-forming agent with a mass fraction of 1.5-2.5%.
[0013] Furthermore, when the chitosan succinic acid complex is prepared, the pH value during the reaction is 6-8, the reaction time is 5-10 minutes, and the reaction temperature is 35-50°C.
[0014] In a preferred embodiment, the phosphate imprinted polymer is prepared by reacting chitosan succinate complex with ferric nitrate at room temperature; 3+ Complexation, then adding sodium phosphate and alkali solution, maintaining at room temperature for 1.5-2.5 hours, to obtain phosphate complexed chitosan succinic acid complex, and then cross-linking reaction with epichlorohydrin at 100-120°C for 0.5-1.5 hours, and then removing phosphate ions to obtain phosphate imprinted polymer; the ratio of chitosan succinic acid complex to epichlorohydrin is 10g:(2.0-2.6)mL.
[0015] The present invention also provides a modified biochar composite membrane prepared by the aforementioned preparation method, and the use of the modified biochar composite membrane in wastewater phosphate treatment, wherein adsorption is achieved through cross-flow circulation filtration; the initial concentration of phosphate in the wastewater is 0.1-10 mg·L -1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11.
[0016] The present invention also discloses an application of a modified biochar composite material in wastewater phosphate treatment. The preparation process of the modified biochar composite material is as follows:
[0017] Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900° C. for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1:(0.3-0.4):(0.3-0.6);
[0018] Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexing and cross-linking through epichlorohydrin, wherein the phosphate imprinted polymer has free hydroxyl groups; the ratio of chitosan succinic acid complex to epichlorohydrin is 10 g:(2.0-2.6) mL; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1:(0.8-0.9);
[0019] The modified biochar and the phosphate imprinted polymer are mixed in a mass ratio of 1:(0.15-0.25), and activated in water vapor at 195-215° C. for 15-35 min to obtain a modified biochar composite material;
[0020] The modified biochar composite material was placed in the phosphate wastewater solution, and the addition amount of the modified biochar composite material was 0.2-3g·L -1 ; The initial concentration of phosphate in wastewater is 0.1-300 mg·L -1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11; the phosphate saturation adsorption capacity of the modified biochar composite material reached 145.1mg·g -1 above.
[0021] Preferably, the modified biochar composite material reduces the phosphate concentration and chemical oxygen demand (COD) in wastewater.
[0022] The present invention provides an application of a modified biochar composite material as a fertilizer returned to the field, and obtains a modified biochar composite material that is completely saturated or nearly saturated in adsorption. Before a farming cycle, the material is placed on the soil surface, and the surface soil with a thickness of 10-15 cm is plowed. The mass ratio of the material to the surface soil is (3-5):100, and then mint seeds are sown.
[0023] Compared with the prior art, the material of the present invention has improved hydrophilicity and improved the removal efficiency of pollutants in wastewater. In addition, after the modified biochar composite material of the present invention adsorbs phosphate ions in high-salt wastewater, the effect of salt leaching on plant growth is significantly reduced compared with traditional biochar materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the growth of seedlings in different soil samples. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0026] The present invention discloses a method for preparing a modified biochar composite membrane, comprising the following steps:
[0027] Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900° C. for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1:(0.3-0.4):(0.3-0.6);
[0028] Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexation and cross-linking through epichlorohydrin, and the phosphate imprinted polymer has free hydroxyl groups; the ratio of chitosan succinic acid complex to epichlorohydrin is 10g:(2.0-2.6)mL; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1:(0.8-0.9); the molar number of succinic anhydride is slightly less than the molar number of chitosan, thereby ensuring that a small part of amino groups in the chitosan skeleton structure of the product are not reacted.
[0029] The modified biochar and the phosphate imprinted polymer are mixed in a mass ratio of 1:(0.15-0.25), and activated in water vapor at 195-215° C. for 15-35 min to obtain a modified biochar composite material;
[0030] The modified biochar composite material is mixed with polyvinylidene fluoride (PVDF) casting solution, and the film is scraped with an automatic film applicator and then quickly placed in an aqueous solution to form a film through a phase conversion method. The film is a modified biochar composite film.
[0031] Preferably, the mass fraction of the modified biochar composite material in the casting solution is 8-12%, the mass fraction of polyvinylidene fluoride (PVDF) in the casting solution is 6-10%, and the casting solution further contains a pore-forming agent with a mass fraction of 1.5-2.5%.
[0032] Preferably, when the chitosan succinic acid complex is prepared, the pH value during the reaction is 6-8, the reaction time is 5-10 min, and the reaction temperature is 35-50°C.
[0033] The preparation process of phosphate imprinted polymer is as follows: chitosan succinate complex reacts with ferric nitrate at room temperature; chitosan succinate complex reacts with Fe 3+ Complexation, then adding sodium phosphate and alkali solution, keeping at room temperature for 1.5-2.5h, obtaining phosphate complexed chitosan succinic acid complex, and then cross-linking reaction with epichlorohydrin at 100-120°C for 0.5-1.5h, and then removing phosphate ions to obtain phosphate imprinted polymer. The ratio of chitosan succinic acid complex to epichlorohydrin is 10g: (2.0-2.6) mL, and the molecular weight of each unit of chitosan succinic acid complex is about 300. Combined with the molecular weight of epichlorohydrin, the above ratio is adopted to make the epichlorohydrin insufficient, so that a small part of the hydroxyl groups of chitosan will not be cross-linked and thus retain a small part of the hydroxyl groups, and then combined with the aforementioned unreacted part of the amino group, so that the chitosan skeleton contains part of the hydroxyl groups and amino groups. Therefore, the phosphate imprinted polymer prepared by the present invention is a relatively special phosphate imprinted polymer.
[0034] By activating the phosphate imprinted polymer and the modified biochar in water vapor at 195-215°C for 15-35 minutes, more active functional groups are obtained on the surfaces of both, and at the same time, the phosphate imprinted polymer and the modified biochar produce a certain degree of cross-linking or other interactions such as hydrogen bonds. The pores of the phosphate imprinted polymer chitosan skeleton increase the overall porosity of the composite material and increase the contact area with the wastewater. More active functional groups and larger porosity can improve the hydrophilicity of the composite material and improve the removal efficiency of pollutants in wastewater.
[0035] The present invention also provides a modified biochar composite membrane prepared by the aforementioned method, and the use of the modified biochar composite membrane in wastewater phosphate treatment, wherein adsorption is achieved through cross-flow circulation filtration; the initial concentration of phosphate in the wastewater is 0.1-10 mg·L -1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11.
[0036] The phosphate saturation adsorption capacity of the modified biochar composite material reached 145.1 mg·g -1 above.
[0037] The modified biochar composite material reduces the phosphate concentration and chemical oxygen demand (COD) in wastewater.
[0038] The present invention also provides an application of a modified biochar composite material as a fertilizer returned to the field, to obtain a modified biochar composite material that is completely saturated or nearly saturated with adsorption. Before the first tillage cycle, the material is placed on the soil surface, and the surface soil with a thickness of 10-15 cm is plowed. The mass ratio of the material to the surface soil is (3-5):100, and then mint seeds are sown.
[0039] In the application as fertilizer, usually if only modified biochar with full or nearly saturated adsorption is used as fertilizer, when the modified biochar is obtained by adsorbing pollutants from high-salt phosphorus-containing wastewater, salt (mainly chloride ions) will also be adsorbed into the modified biochar, and then when the plants are planted, the salt particles in the modified biochar will be released into the soil, thereby causing adverse effects on plant growth. However, the present invention greatly reduces the adverse effects on plant growth of the modified biochar composite material that is fully or nearly saturated in adsorption of high-salt phosphorus-containing wastewater after returning it to the field as fertilizer by compounding and co-activating a special phosphate imprinted polymer with the modified biochar.
[0040] The special phosphate imprinted polymer obtained by the present invention containing a small amount of free amino groups and hydroxyl groups shows a stronger function of reducing COD when mixed with modified biochar, compared with the commonly used phosphate imprinted polymer that is completely cross-linked and basically does not contain free amino groups and hydroxyl groups.
[0041] Example 1 Preparation of modified biochar composite material
[0042] 85.7g dolomite powder was added to a mixture of 200g peanut shell powder and bentonite (the mass ratio of peanut shell powder to bentonite was 3:1), and ground until the mixture was uniform. Then it was placed in a crucible in a tube furnace, heated to 900℃ at a rate of 5℃ / min under oxygen-limited conditions, kept for 1h, and then naturally cooled to room temperature, ground through a 100-mesh sieve, and marked as modified biochar (BC).
[0043] Dissolve 10 g of chitosan in acetic acid aqueous solution (1%, 1000 mL), add 50 mmol of succinic anhydride and 50 mL of pyridine while stirring, control the pH to 6.5, react at 40°C for 10 min, terminate the reaction, and obtain chitosan succinic acid complex (infrared spectroscopy IR verifies that chitosan and succinic acid form an amide bond).
[0044] 10g chitosan succinate complex was dissolved in 5% acetic acid, 20g Fe(NO3)3·9H2O was slowly added at room temperature and stirred continuously, and then 90g Na3PO4·12H2O (phosphate as template ion) was added. 1000mL 1M sodium hydroxide aqueous solution was slowly dripped into the mixture and stirred at 200r / min for 3h. Filtered and vacuum dried to obtain phosphate complex chitosan succinate complex (the amide group of chitosan succinate complex was verified to be complexed with Fe ions by Fourier transform infrared spectroscopy (FTIR) spectrum), and then cross-linked with 2.2mL epichlorohydrin and 2000mL 5% acetic acid at 115℃ oil bath reflux for 1h. The reaction product was washed with 1M potassium hydroxide solution and deionized water successively to complete the removal of phosphate ions, and the phosphate imprinted polymer was obtained, dried, crushed, passed through a 100-mesh sieve, and marked as PJ.
[0045] 50 g of modified biochar was mixed with 10 g of phosphate imprinted polymer, activated in water vapor at 200 °C for 20 min, dried, crushed, and passed through a 100-mesh sieve to obtain a modified biochar composite material, labeled BC-PJ.
[0046] Example 2 Preparation of modified biochar composite membrane
[0047] 55.6g of BC-PJ prepared in Example 1 was added to 450g of N,N-dimethylformamide (DMF), and magnetically stirred for 2h at room temperature to form a stable suspension, and then 40g of polyvinylidene fluoride (PVDF) and 10g of polyethylene glycol (PEG) were slowly added, and stirring was continued for 2h until it was completely dissolved as a casting solution. Subsequently, ultrasonication was performed for 1h and vacuum degassing was performed for 0.5h to remove bubbles in the solution. Next, the mixed solution was coated on a smooth glass plate with a 200μm film applicator, and then immediately placed in a 10% ethanol solution to form a film, and then allowed to stand for 12h to ensure sufficient solvent replacement, and finally dried naturally, and marked as PVDF-BC-PJ.
[0048] Comparative Example 1
[0049] 85.7g dolomite powder was added to a mixture of 200g peanut shell powder and bentonite (the mass ratio of peanut shell powder to bentonite was 3:1), and ground until the mixture was uniform. Then it was placed in a crucible in a tube furnace, heated to 900℃ at a rate of 5℃ / min under oxygen-limited conditions, kept for 1h, and then naturally cooled to room temperature, ground through a 100-mesh sieve, and marked as modified biochar (BC).
[0050] Comparative Example 2
[0051] Compared with Example 1, succinic anhydride was changed to 60 mmol; epichlorohydrin was changed to 50 mL (excess).
[0052] Comparative Example 3
[0053] Compared with Example 1, the 200° C. steam activation step is removed.
[0054] Comparative Example 4
[0055] It is basically the same as Example 2, except that the material prepared in Comparative Example 1 is used to replace BC-PJ.
[0056] Comparative Example 5
[0057] It is basically the same as Example 2, except that the material prepared in Comparative Example 2 is used to replace BC-PJ.
[0058] Comparative Example 6
[0059] It is basically the same as Example 2, except that the material prepared in Comparative Example 3 is used to replace BC-PJ.
[0060] Application Example 1 Contact angle and mechanical properties of modified biochar composite membrane
[0061] The surface hydrophilicity of the membrane was analyzed using a contact angle meter (CA200, China). The specific steps were as follows: the dried composite membrane was cut into a square with a side length of 1 cm and then attached to a glass slide, which was placed on the sample stage of the meter. After deionized water was dropped onto the sample surface for 3 seconds, an image was collected and the contact angle was calculated.
[0062] After measurement, the contact angles of pure PVDF membrane (without any other materials), Example 2, and the composite membranes of Comparative Examples 4-6 were 95.8°, 90.1°, 101.2°, 96.4°, and 100.5°, respectively. It can be seen that the contact angle of Comparative Example 4 containing only modified biochar is lower than that of pure PVDF membrane, and the contact angles of Comparative Example 5 containing modified biochar and conventional phosphate imprinted polymer and Comparative Example 6 without 200°C steam activation are also lower than that of pure PVDF membrane. The hydrophilicity of Example 2 containing modified biochar and the homemade phosphate imprinted polymer of the present invention is improved compared with pure PVDF membrane.
[0063] The mechanical properties of pure PVDF membrane and composite membrane were tested using an electronic universal material testing machine (instron 3367, USA). The membrane samples were cut into strips with a width of 15 mm and a length of 60 mm. The thickness of the membrane was measured with a thickness gauge (awt-chy01), and then the mechanical properties were tested using an electronic universal material testing machine. The initial clamping distance of the membrane was 40 mm, and the tensile rate was 2 mm·s -1 Each film was tensile tested 3 times. The tensile strength and elongation at break were calculated.
[0064] The tensile strengths of pure PVDF membrane (without any other materials), Example 2, and Comparative Examples 4-6 composite membranes were 0.46MPa, 0.72MPa, 0.58MPa, 0.66MPa, and 0.64MPa, respectively, and the fracture growth rates were 4.5%, 7.2%, 5.4%, 6.6%, and 6.5%, respectively. It can be seen that the compounding and co-activation of the special phosphate imprinted polymer and the modified biochar can improve the mechanical properties of the composite membrane to a certain extent.
[0065] Application Example 2 Phosphate adsorption and COD reduction performance of modified biochar composites
[0066] 1) Simulate phosphate wastewater and prepare phosphate solutions with different concentrations (10 mg·L -1 , 50mg·L -1 、100mg·L -1 , 200mg·L -1 、300mg·L -1 , 400mg·L -1 ), pH 8.0, room temperature, shaking for 24 h, and the concentration of modified biochar composite material was 1.6 g·L -1 .
[0067] The maximum phosphate adsorption capacity of the modified biochar composite materials of Example 1 and Comparative Examples 1-3 for saturated adsorption was 145.1 mg·g -1 , 103.2mg·g -1 , 124.5mg·g -1 , 113.7mg·g -1 .
[0068] 2) Simulate phosphate wastewater and prepare 50 mg·L -1 Phosphate solution, pH 8.0, room temperature, shaking for 30 min, modified biochar composite material concentration of 1.6 g·L -1 .
[0069] After testing, the phosphate removal rates of the composite materials of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were 99.3%, 90.5%, 93.3%, and 92.8%, respectively. It can be seen that the short-term phosphate removal rate of Example 1 is already high and meets the wastewater discharge standard.
[0070] 3) Simulate phosphate wastewater and prepare 100 mg·L -1 Phosphate solution, room temperature, shaken for 2 h, pH values were 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, and the concentration of modified biochar composite material was 1.6 g·L -1 .
[0071] After testing, the pH values were 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, and 12.0, and the removal rates of phosphate radicals by the composite material of Example 1 were 23.4%, 67.2%, 89.4%, 92.9%, 94.8%, 97.7%, 99.6%, 100%, 99.7%, 97.8%, 92.3%, and 81.3%, respectively. It can be seen that the performance of the composite material of Example 1 in removing phosphate radicals from the solution is less affected by pH value, and phosphate radicals can be adsorbed in a wide pH range.
[0072] 4) Take wastewater from a farm in Nanjing and dilute it to a phosphate concentration of 60.5 mg·L -1 , COD is 150mg·L -1 , pH 8.0, room temperature, shaking for 30 min, the concentration of modified biochar composite material was 1.6 g·L -1 .
[0073] It was measured that the phosphate removal rates of the composite materials of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were 99.9%, 92.4%, 94.9% and 93.6% respectively.
[0074] After the composite materials of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were treated, the final COD concentrations became 27.3%, 50.4%, 41.7% and 45.9% of the initial COD concentrations, respectively.
[0075] Application Example 3 Filtration and separation performance of modified biochar composite membrane
[0076] 1) Circulation cross-flow experiment
[0077] The phosphate filtration performance of the membrane was tested using a cross-flow filtration device. The experiment was carried out in a triple plate apparatus. The solutions used were 1 mg·L -1 and 5mg·L -1 phosphate solution (3 composite membranes were placed in 2L phosphate solution, and the surface area of each composite membrane was 70cm 2 , the film thickness is about 140 μm), when the solution used is 1 mg·L -1 When the material obtained in Comparative Example 4 was filtered for 6h, 12h, 18h, and 24h, the phosphate concentrations in the solution were 0.51 mg·L -1 , 0.23mg·L -1 , 0.17mg·L -1 , 0.17mg·L -1 The phosphate concentrations in the solution of the material obtained in Example 2 after treatment for 6h, 12h, 18h, and 24h were 0.36mg·L -1, 0.17mg·L -1 , 0.10mg·L -1 , 0.10mg·L -1 When the solution used is 5 mg·L -1 When the material obtained in Comparative Example 4 was filtered for 6h, 12h, 18h, and 24h, the phosphate concentrations in the solution were 3.5 mg·L -1 , 2.9mg·L -1 , 2.7mg·L -1 , 2.7mg·L -1 The phosphate concentrations in the solution of the material obtained in Example 2 after treatment for 6 h, 12 h, 18 h, and 24 h were 2.8 mg·L -1 , 2.1mg·L -1 、1.6mg·L -1 、1.6mg·L -1 .
[0078] 2) Cyclic stability test
[0079] At 1 mg·L -1 The ultrafiltration membrane was immersed in 1L of 1mol / L NaOH solution after filtration and adsorption saturation. The desorption rate was calculated after 3h. Then the membrane was rinsed with pure water until neutral and placed in a triple plate instrument for 1mg·L -1 Repeat the above steps to calculate the desorption rate of each cycle.
[0080] The material obtained in Example 2 has better cycle stability than the material obtained in Comparative Example 4. The desorption rates of the material obtained in Example 2 after 5 cycles were 87%, 87%, 86%, 86%, and 85%, respectively, while the desorption rate of the material obtained in Comparative Example 4 decreased from 78% to 71% after 5 cycles.
[0081] Application Example 4: After the modified biochar composite material is saturated with adsorption, it is returned to the field for use as fertilizer
[0082] Simulate high-salinity phosphate wastewater and prepare phosphate concentration of 300 mg·L -1 , NaCl concentration is 25 g·L -1 The high-salinity phosphate wastewater, pH 8.0, room temperature, shaking for 24 h, the concentration of modified biochar composite material was 1.6 g·L -1 When the modified biochar composite material comes from Example 1, an adsorption saturated modified biochar composite material is obtained. When the modified biochar composite material comes from Comparative Example 1, a saturated adsorption material of Control Group 1 is obtained.
[0083] Application Example 2: 1) Treatment of phosphate concentration 300 mg·L -1 The obtained saturated adsorption material was used as the saturated adsorption material of control group 2.
[0084] At room temperature, 13g of the adsorption saturated modified biochar composite material, the material of control group 1, the material of control group 2 or commercial organic fertilizer were mixed with 250g of soil, and only 250g of soil was added as a blank control group. The same number of mint seeds were scattered in the above soil samples, and 35mL of tap water was added to the flowerpot every 3 days. The pH value was controlled at 7.0. After 30 days, the growth of 5 groups of mint was observed to evaluate the nutrient slow-release performance of the composite material. Five parallel experiments were set up in each group, and the results were averaged.
[0085] After 30 days, the leaf size and density of mint were counted. The growth of seedlings in different soil samples was ranked as follows: blank control group < commercial organic fertilizer < control group 1 < adsorption saturated modified biochar composite material < control group 2.
[0086] like Figure 1 As shown, the leaf width and rhizome length of the blank control group were 0.42 cm and 5.5 cm, respectively, the leaf width and rhizome length of the commercial organic fertilizer group were 0.82 cm and 7.4 cm, respectively, the leaf width and rhizome length of the control group 2 were 1.35 cm and 10.6 cm, respectively, the leaf width and rhizome length of the control group 1 were 0.97 cm and 7.8 cm, respectively, and the leaf width and rhizome length of the adsorption saturated modified biochar composite material group were 1.31 cm and 10.1 cm. The above test data show that after the modified biochar composite material of the present invention adsorbs high-salt phosphate wastewater, the effect of salt leaching on plant growth is significantly reduced compared with traditional biochar materials.
[0087] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a modified biochar composite membrane, characterized in that: The steps include: Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900°C for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1: (0.3-0.4): (0.3-0.6); Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexing and cross-linking by epichlorohydrin, wherein the phosphate imprinted polymer has free hydroxyl groups; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1:(0.8-0.9); The modified biochar and the phosphate imprinted polymer are mixed in a mass ratio of 1:(0.15-0.25), and activated in water vapor at 195-215°C for 15-35 minutes to obtain a modified biochar composite material; The modified biochar composite material is mixed with polyvinylidene fluoride (PVDF) casting solution, and the film is scraped with an automatic film applicator and then quickly placed in an aqueous solution to form a film through a phase conversion method. The film is a modified biochar composite film.
2. The method for preparing a modified biochar composite membrane according to claim 1, characterized in that: The mass fraction of the modified biochar composite material in the casting solution is 8-12%, the mass fraction of polyvinylidene fluoride (PVDF) in the casting solution is 6-10%, and the casting solution also contains a pore-forming agent with a mass fraction of 1.5-2.5%.
3. The method for preparing a modified biochar composite membrane according to claim 1, characterized in that: When the chitosan succinic acid complex is prepared, the pH value during the reaction is 6-8, the reaction time is 5-10 minutes, and the reaction temperature is 35-50°C.
4. The method for preparing a modified biochar composite membrane according to claim 1, characterized in that: The preparation process of phosphate imprinted polymer is as follows: chitosan succinate complex reacts with ferric nitrate at room temperature; chitosan succinate complex reacts with Fe 3+ Complexation, then add sodium phosphate and alkali solution, keep at room temperature for 1.5-2.5h to obtain phosphate complexed chitosan succinic acid complex, and then cross-link with epichlorohydrin at 100-120℃ for 0.5-1.5h, and then remove phosphate ions to obtain phosphate imprinted polymer; the ratio of chitosan succinic acid complex to epichlorohydrin is 10g: (2.0-2.6)mL.
5. The modified biochar composite membrane obtained by the preparation method according to any one of claims 1 to 4.
6. The use of the modified biochar composite membrane according to claim 5 in wastewater phosphate treatment, characterized in that: Adsorption is achieved by cross-flow circulation filtration; the initial phosphate concentration in the wastewater is 0.1-10 mg•L −1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11.
7. Application of a modified biochar composite material in wastewater phosphate treatment, characterized in that: The preparation process of modified biochar composite material is as follows: Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900°C for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1: (0.3-0.4): (0.3-0.6); Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexing and cross-linking by epichlorohydrin, wherein the phosphate imprinted polymer has free hydroxyl groups; the ratio of chitosan succinic acid complex to epichlorohydrin is 10 g: (2.0-2.6) mL; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1: (0.8-0.9); The modified biochar and the phosphate imprinted polymer are mixed in a mass ratio of 1:(0.15-0.25), and activated in water vapor at 195-215°C for 15-35 minutes to obtain a modified biochar composite material; The modified biochar composite material was placed in the phosphate wastewater solution, and the addition amount of the modified biochar composite material was 0.2-3g•L −1 ; The initial concentration of phosphate in wastewater is 0.1-300 mg•L −1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11; the phosphate saturation adsorption capacity of the modified biochar composite material reached 145.1mg•g −1 above.
8. The use according to claim 7, characterized in that: The modified biochar composite material reduces the phosphate concentration and chemical oxygen demand (COD) in wastewater.
9. Application of modified biochar composite material as fertilizer for returning to fields, characterized in that: A modified biochar composite material with complete or nearly saturated adsorption is obtained. Before the first tillage cycle, the material is placed on the soil surface, and the surface soil with a thickness of 10-15 cm is plowed. The mass ratio of the material to the surface soil is (3-5):100, and then mint seeds are sown; The process of obtaining the modified biochar composite material with complete or nearly saturated adsorption is as follows: the modified biochar composite material is placed in the phosphate wastewater solution, and the addition amount of the modified biochar composite material is 0.2-3 g•L −1 ; The initial concentration of phosphate in wastewater is 0.1-300 mg•L −1 , adsorption time 0.5-20h, phosphate wastewater pH 3-11; the phosphate saturation adsorption capacity of the modified biochar composite material reached 145.1mg•g −1 above; The preparation process of modified biochar composite material is as follows: Peanut shell powder, bentonite powder and dolomite powder are uniformly mixed and pyrolyzed at 700-900°C for 1-2 hours to obtain modified biochar; the mass ratio of peanut shell powder, bentonite powder and dolomite powder is 1: (0.3-0.4): (0.3-0.6); Chitosan succinate complex and Fe 3+ The phosphate imprinted polymer is prepared by complexing and cross-linking by epichlorohydrin, wherein the phosphate imprinted polymer has free hydroxyl groups; the ratio of chitosan succinic acid complex to epichlorohydrin is 10 g: (2.0-2.6) mL; the chitosan succinic acid complex is synthesized from chitosan and succinic anhydride; the molar ratio of chitosan to succinic anhydride is 1: (0.8-0.9); The modified biochar and the phosphate imprinted polymer were mixed in a mass ratio of 1:(0.15-0.25), activated in water vapor at 195-215° C. for 15-35 minutes, and obtained a modified biochar composite material.
Citation Information
Patent Citations
Chitosan / anhydride modified biological carbon composite and preparation method and application thereof
CN106890624A
Preparation method and application of phosphorus-accumulating bacteria imprinting biological carbon
CN107129982A